Evolution of HIV/AIDS cases in people aged 50 years and over attended at a university hospital in the Northeast of Brazil - Santos , Linda Djeyme (2021)
This study aims to analyze the evolution of individuals over 50 years of age or older diagnosed with infection by the Human Immunodeficiency Virus / Acquired Immunodeficiency Syndrome (HIV / AIDS) at a University Hospital in the Northeast of Brazil, this is a descriptive, documental epidemiological study with a quantitative approach, from a historical series from 2006 to 2016. The data were collected through the hospital epidemiology core database. The study showed a progressive increase in the evolution of individuals with 50 years of age or older who are diagnosed with HIV/AIDS, the most affected being men in the age group between 50 and 59 years, heterosexual. It is concluded that to assist individuals who are in the process of aging, who are sexually active and surrounded by prejudices, requires the attitude of professionals who are increasingly prepared, open to new paradigms and with knowledge of the particularities presented by them.